2022
DOI: 10.1186/s12978-022-01419-5
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression among pregnant adolescents and women living with HIV in rural KwaZulu-Natal, South Africa: a cross sectional study to assess progress towards UNAIDS indicators and Implications for HIV Epidemic Control

Abstract: Background South Africa has made significant progress in scaling up antiretroviral therapy (ART) to achieve the aspirational goal of HIV epidemic control. The aim of this study was to determine the prevalence of HIV, assess progress towards each of the Joint United Nations Programme on HIV/AIDS (UNAIDS) indicators and determine factors associated with achieving viral suppression among pregnant adolescents and women living with HIV in rural KwaZulu-Natal, South Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Viral load suppression is reported in married women, suggesting a presence of social support structures that encourage disclosure of HIV-positive status to partners facilitating adherence to ART [22,27,28]. These previous findings highlight the need for targeted approaches to reach different key groups of PLOS GLOBAL PUBLIC HEALTH female individuals, specifically those in the younger age groups [22,[26][27][28] to improve viral load suppression rates.…”
Section: Plos Global Public Healthmentioning
confidence: 85%
See 3 more Smart Citations
“…Viral load suppression is reported in married women, suggesting a presence of social support structures that encourage disclosure of HIV-positive status to partners facilitating adherence to ART [22,27,28]. These previous findings highlight the need for targeted approaches to reach different key groups of PLOS GLOBAL PUBLIC HEALTH female individuals, specifically those in the younger age groups [22,[26][27][28] to improve viral load suppression rates.…”
Section: Plos Global Public Healthmentioning
confidence: 85%
“…Facilities should find the missing men in communities who disengage from health seeking [25]. Most antenatal studies in South Africa have been used to evaluate viral load suppression in women [22,26,27]. Across the studies, adolescent girls, and young women (AGYW) have reported the lowest viral suppression rates [22,26,27].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent patients with perinatally acquired HIV are also known to have a higher incidence of poor compliance with antiretroviral drugs [ 37 , 38 ]. Previous studies found lower rates of viral suppression among adolescent patients living with HIV [ 39 , 40 ]. Van Wyk et al also suggest that adolescents aged 15–19 years have the poorest compliance with HIV treatment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%